Student Career Planning After Bachelor Graduation - Dinda Cahya Novianti; Kristina Natalia Panjaitan; Nathasya Devana (International Conference on Psychology and Education (ICPE), 2023)
Career planning is an individual's conscious process of making future career decisions. Career planning is a personal process in determining their career goals, as well as what paths or steps they should take to reach their career goals so they don't choose the wrong target. Things that can affect career development are self-view, points, responses, opinions, skills possessed and all beliefs when determining the career direction that has been set, also including the stages that take place due to the influence of influences within the individual and encouragement that is outside the individual the. This research was conducted using qualitative methods. The ways of collecting data are observation, interviews, and literature review. Data were analyzed using a data triangulation method. As for the informants in the study, there were 3 students at Surabaya State University. The results of the study show that students already have a career plan starting from self-introduction and the world of work. The resource persons have a mature career plan and will immediately implement it when they graduate from college. With proper career planning, the resource persons are ready to enter the world of work. With careful planning and good preparation in determining a career, the chances of activation are reduced.